AB0539 Psychological status evaluation in spondylarthritis tunisian patients and relationship with diseases features. (23rd January 2014) - Mahmoud, I.; Dridi, L.; Saidane, O.; Tekaya, R.; Sahli, H.; Abdelmoula, L.; Chaabouni, L.; Zouari, R.
Abstract : Background: The prevalence of psychological disorders is greater in patients with rheumatologic conditions than among the general population. Objectives: We aim in this study to determine the frequency of depression and anxiety disorders in spondylarthritis (SA) patients and to determine predictor disease parameters. Methods: We performed a cross-sectional monocentric study in 70 SA Tunisian patients. Presence of anxiety or depression disorders was evaluated by the Hospital Anxiety and Depression Scale score (HADS). A certain anxious or depression state was defined by a HADS>10. Epidemiological factors of SA and different disease assessing measures were noted. For statistical analysis, we used Khi 2 -test for qualitative variables and Student-test for quantitative variables. A p value≤0, 05 was considered significant. Results: There were 65% men and 35% women. Age ranged from 16 to 74 years with an average of 40, 6 years. Disease mean duration was 10, 75±9 years. Mean HADS score was 15, 9 and 49 patients had HADS score >10 (certain depression or anxious state) corresponding to a frequency of 70%. 63% of patients had peripheral joints involvement and 65% had hips involvement. Mean Pain-VAS was 65mm and mean Tirederness-VAS was 56mm. Mean BASDAI score was 45%, mean BASFI score 44, 7% and mean BASG-s score 55%. The mean BASMI score was 4, 76 and the mean BASRI score 4, 43. Statistical analysis showed that presence of depression or anxious state was correlated best with BASG-s (p=0, 00006), followed by BASFI (p=0, 001). Depression and anxiety were significally higher in female (p=0, 02) and in patients with active disease (BASDAI>40%) (p=0, 009). Depression or anxious status was correlated with Tiredness-VAS (p=0, 004) and not with Pain-VAS (p=0, 171). Psychological status was independent of disease duration (p=0, 959), spine mobility (BASMI) (p=0, 567) and of the severity of radiologic involvement (BASRI) (p=0, 237). No correlation was seen with peripheral joints involvement nor with hips involvement (respectively p=0, 914 and 0, 660). Conclusions: Frequency of depression and anxiety disorders in SA is high. Female gender, general well- being, disease activity and functional impairment are predicting factors. Disclosure of Interest: None Declared